Micro-propagation of aquatic plant Brazilian micro sword ( Lileaopsis brasiliensis ) - Ing, Nguang Siew; Dhiya Dalila, Zawawi; Chew, Ha Hou; Rokiah, Zainuddin (2019)
Lileaopsis brasiliensis is one of the ornamental aquatic plants and yet still being commercialized in Malaysia because of the grassy foreground features. This study is conducted to propagate higher quantity and quality of L. brasiliensis and to determine the optimum concentration of plant growth regulator for the micro-propagation in Murashige and Skoog (MS) (1962) basal media with different concentration of Naphteneacetic acid (NAA) and 6- Benzylaminopurine (BAP) for four weeks period following with subculture procedure. All treatments for 1 L MS media were adjusted to pH 5.7-5.8, adding sucrose and pytagel with 30 g/L and 2.5 g/L, respectively. The explants were sub-cultured at least three times within five months. The results of the quality and quantity of this species within different concentration of NAA and BAP have been determined. For shoot regeneration, the highest number of shoot induced in initial culture (C0), first (C1), second (C2) and the third subculture (C3) were 103, 102, 104 and 137 respectively. There was no significant different of shoot regeneration in different concentration of NAA and BAP combination. However, the high number of shoot regeneration was obtained from the following concentration NAA: BAP: zero concentration in both C0 (103.0±5.3) and C2 (104.0±14.2), 1.5: 0.0 mg/L with 102.0±4.4 and1.5:0.5 mg/L with 137.0±41.2 in C1 and C3, respectively. Based on the results, it can be concluded that shoot regeneration was observed even though in very low concentration of NAA and BAP.